Goat in a boat - Trasler, Janee (New York : Scholastic Inc., 2020)
When Goat appears wearing a raincoat and invites all the animals to go for a boat ride on a sunny day, Dog declines but as heavy rain falls, Dog needs a boat, too.
Ages 4-6.
Grades K-1.
Keywords: Rain and rainfall -- Fiction; Boats and boating -- Fiction; Floods -- Fiction; Frogs -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Rain and rainfall -- Juvenile fiction; Boats and boating -- Juvenile fiction; Floods -- Juvenile fiction; Frogs -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Readers (Publications); Picture books; Animal fiction